Effect of Plant Residues on AM Fungi - Vaidya, Geeta Shrestha; Shrestha, K; Wallander, H (Scientific World, 2010)
In this study we have investigated the effect of organic matter on growth of an arbuscular mycorrhizal (AM) fungi in eroded slopes in Nepal such as Forest in Kavre District. Different types of organic matter (leaves of Thitonia diversifolia, Eupatorium adenophorum, Lantana camara, farm compost) and tri-superphosphate were mixed with eroded soil. The mesh bags were buried around trees of eroded site. The mesh bags were harvested after 6 months and the AM fungi in the mesh bags was quantified by analysing the AM spores. Key words: Organic matters; Arbuscular mycorrhizal fungi; Fertilizers and forest. DOI: 10.3126/sw.v6i6.2640 Scientific World, Vol. 6, No. 6, July 2008 85-88